Effect of Aerobic Exercise on Major Depression in Patients with Mild Alzheimer’s Disease - Ali Shawesh,; Wael Elwahshe, (AlQalam Journal of Medical and Applied Sciences, 2026)
Alzheimer's disease (AD), the leading cause of dementia, represents a significant source of morbidity and mortality in the elderly population. Emerging evidence suggests depression may be a risk factor for cognitive impairment and AD progression. While physical activity is generally recognized for its mood-enhancing properties, its specific role in managing depression in AD patients requires further investigation. This study aimed to evaluate the effect of structured aerobic exercise as an adjunctive therapy for major depression in patients with mild Alzheimer's disease. In a randomized controlled trial, 40 participants (age range: 60-80 years) diagnosed with major depression and mild AD were allocated into two groups. The experimental group (n=20) received a combination of antidepressant medication (SSRI) and a supervised aerobic exercise program, consisting of treadmill walking for 30 minutes at 3.5 km/h, three times per week for four weeks. The control group (n=20) received antidepressant medication only. The primary outcome, depression severity, was measured at baseline, at 2 weeks, and at 4 weeks post-intervention using the HDRS. While both groups showed significant improvements in HDRS scores from baseline (p<0.0001), the experimental group demonstrated a significantly greater reduction in depression scores compared to the control group post-intervention (p=0.001). The mean decrease in the HDRS score was 20.53 points in the exercise group versus 8.13 points in the medication-only group. A structured aerobic exercise program, when combined with pharmacotherapy, is a significantly more effective intervention for reducing depressive symptoms in patients with mild Alzheimer's disease than pharmacotherapy alone. These findings support the integration of supervised aerobic exercise into standard treatment regimens for managing major depression in this patient population.